Pelestarian Dan Ekspansi Pasar Batik Tulis Gedhog Tuban Di Era Globalisasi - ., Karsam (LPPM Universitas PGRI Adi Buana Surabaya, 2014)
Batik Gedhog is a traditional batik in the District Kerek, Tuban. Fabric of batik gedhog has a rough surface because it is made by hand. Motif batik gedhogtends to follow the flow pat-terned geometric rough cloth. Seeing by this condition, the authors worrybatik gedhog will be expire ev- erlasting. On the basis of this research was conducted by reviewing about, first, how the traditional batik ‘batik gedhog Tuban, both how business should be done to preserve the traditional batik Tuban , namely Batik Gedhog in this era of globalization and to address mar-ket expansion. Objectives is to find strategies or ways for traditional batik preservation, namely batik gedhog Tuban in the present and the future , so batik gedhog Tuban can enterthe market competition in today’s global economy era. To answer these problems the authors conducted research using qualitative descriptive methods. Several attempts to preserve batik gedhog Tuban is to improve the quality of fabric, pattern in the current era motif now, promo-tion, exhibition and increase brand emage. This study is expectedto be useful for the readers and the batik gedhog markers Tuban.